2010
DOI: 10.1063/1.3484152
|View full text |Cite
|
Sign up to set email alerts
|

Formation of low-resistance Ohmic contacts to N-face n-GaN for high-power GaN-based vertical light-emitting diodes

Abstract: We report on the formation of low-resistance Ohmic contacts to N-face n-GaN for high-power vertical light-emitting diodes using an Al–Ga solid solution (50 nm)/Ti(30 nm)/Al(200 nm) scheme and compare them with Ti(30 nm)/Al(200 nm) contacts. The Al–Ga solid solution layer is introduced to minimize the formation of Ga vacancies near the N-face n-GaN surface. It is shown that, unlike the Ti/Al contacts, the Al–Ga solid solution/Ti/Al contacts exhibit Ohmic behavior with a resistivity of 4.1×10−4 Ω cm2, even after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Jeon et al 15 showed that the use of TiN/Al contacts exhibited better electrical behaviors than did Ti/Al contacts when annealed at 300 C. The electrical degradation of the Ti/Al contacts to N-face n-GaN annealed at temperatures in the range of 300 -500 C was attributed to the presence of acceptorlike Ga vacancies near the n-GaN surface region caused by the outdiffusion of Ga. 16 This implies that preventing the Ga atoms from outdiffusing from N-face n-GaN would allow low-resistance ohmic contacts to N-face n-GaN to be formed. Jeon et al 17 used Ga atoms-containing Al layer (namely, an Al-Ga solid solution layer) to suppress the outdiffusion of Ga atoms from n-GaN. They showed that unlike Ti/Al contacts, the Al-Ga solid solution/Ti/Al contacts remained ohmic after annealing at 250 C. Thus, in this work, we investigated the effect of Ti(Ga) solid solution and TiN layers on the electrical properties of Ti/Al-based contacts.…”
Section: Introductionmentioning
confidence: 98%
“…Jeon et al 15 showed that the use of TiN/Al contacts exhibited better electrical behaviors than did Ti/Al contacts when annealed at 300 C. The electrical degradation of the Ti/Al contacts to N-face n-GaN annealed at temperatures in the range of 300 -500 C was attributed to the presence of acceptorlike Ga vacancies near the n-GaN surface region caused by the outdiffusion of Ga. 16 This implies that preventing the Ga atoms from outdiffusing from N-face n-GaN would allow low-resistance ohmic contacts to N-face n-GaN to be formed. Jeon et al 17 used Ga atoms-containing Al layer (namely, an Al-Ga solid solution layer) to suppress the outdiffusion of Ga atoms from n-GaN. They showed that unlike Ti/Al contacts, the Al-Ga solid solution/Ti/Al contacts remained ohmic after annealing at 250 C. Thus, in this work, we investigated the effect of Ti(Ga) solid solution and TiN layers on the electrical properties of Ti/Al-based contacts.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] Especially, GaNbased light emitting diodes (LEDs) have been extensively used for full color displays, light sources for traffic-light lamps, and headlamps for vehicles. However, conventional top-emission LEDs suffer from undesirable problems such as current crowing, voltage drop, and poor heat dissipation under high current operation.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based light emitting diodes (LEDs) have been extensively used for full color displays, light sources for traffic-light lamps, and headlamps for vehicles. The performance and reliability of GaN LEDs and laser diodes depends strongly on the quality of the p-Ohmic contact [1][2][3][4][5][6][7][8][9][10] . For low hole concentration materials like p-GaN, high work function metals such as Ni, Pd, Cr and Pt with an overlayer of Au are required for low resistivity contacts [4][5][6][7][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%